2014
DOI: 10.2319/120913-905.1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of surgically assisted maxillary protraction vs regular facemask

Abstract: Long-term results of surgically assisted maxillary protraction vs regular facemask Ş irin Nevzatog lu a ; Nazan Kü çü kkeleş b ABSTRACT Objective: To evaluate the short-and long-term treatment results of rapid maxillary expansion (RME) and surgical assistance during maxillary protraction with a facemask (FM). Materials and Methods: This study was carried out in 28 patients (12 male, 16 female) with maxillary retrognathism, anterior crossbite, and Class III skeletal and dental malocclusion characteristics. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
1
14
2
1
Order By: Relevance
“…By the end of the treatment, the majority of patients maintained their initial vertical growth pattern, showing some changes in growth direction, mainly in those with neutral rotation. Of the former, some patients shifted toward having clockwise growth direction, whereas others had counterclockwise growth direction; suggesting that in response to therapy, changes toward clockwise mandibular rotations should not always be expected, as previously reported by others (Kiliçoglu & Kirliç, ; Nevzatoğlu & Küçükkeleş, ; Wolfe et al, ).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…By the end of the treatment, the majority of patients maintained their initial vertical growth pattern, showing some changes in growth direction, mainly in those with neutral rotation. Of the former, some patients shifted toward having clockwise growth direction, whereas others had counterclockwise growth direction; suggesting that in response to therapy, changes toward clockwise mandibular rotations should not always be expected, as previously reported by others (Kiliçoglu & Kirliç, ; Nevzatoğlu & Küçükkeleş, ; Wolfe et al, ).…”
Section: Discussionsupporting
confidence: 64%
“…Maxillary protraction with FM in conjunction with rapid palatal expansion (RPE) is a currently used therapy for Class III patients with hypoplasia or maxillary retrusion. Studies comparing treated patients with an untreated control group have shown RPE/FM therapy to be effective, especially when used at an early age (Cordasco et al, 2014;Kiliçoglu & Kirliç, 1998;Mandall et al, 2010;Nevzatoğlu & Küçükkeleş, 2014). Additionally, RPE/FM therapy has also been reported to reduce the need of subsequent surgical treatment (Mandall et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-angle Class III patients who exhibit severe retrognathism of the maxilla, patients who have lost chance of orthopedic correction, and patients who refuse to undergo orthognathic surgeries are candidates for corticotomy-assisted maxillary protraction [ 50 ]. Sutural distraction osteogenesis versus osteotomy distraction osteogenesis for protraction of midface has already been used.…”
Section: Appliancesmentioning
confidence: 99%
“…Significant relapse of maxillary advancement was detected in a 6-year follow-up. However, well-preserved dental relationship was reported [ 54 ].…”
Section: Appliancesmentioning
confidence: 99%